Convex games, clan games, and their marginal games - Rodica Branzei; Dinko Dimitrov (Bielefeld University, Institute of Mathematical Economics (IMW), 2005)
We provide characterizations of convex games and total clan games by using properties of their corresponding marginal games. As it turns out, a cooperative game is convex if and only if all its marginal games are superadditive, and a monotonic game satisfying the veto player property with respect to the members of a coalition C is a total clan game (with clan C) if and only if all its C-based marginal games are subadditive.
urn:nbn:de:hbz:361-7332
Keywords: C71; 330; Characterization; Convex games; Marginal games; Subadditive games; Superadditive games; Total clan games; Nichtkooperatives Spiel; Koalition; Theorie